Potenciación del sistema de seguimiento mediante la integración del proceso de programación y ejecución con enfoque territorial para optimizar la estrategia de intervención basada en resultados de la GRD en la educación peruana: un análisis del año 2021 -2022 - Valencia Llalla, Jakeline Yhanira (2024)
Attention towards danger and/or disaster arises when these concepts materialize and cause harm to the population. It is at this point that authorities, parents, mothers, and children question how to turn back time to prepare, prevent, and mitigate the effects of the disaster. In this regard, the education sector, which harbors a significant portion of the population, serves as the center of knowledge where students are prepared for an uncertain future. From this perspective, the idea emerges to undertake an innovative project that quantitatively and qualitatively showcases the ongoing efforts in disaster risk management within the education sector, starting nationally and cascading down to the educational community. The objective is to highlight efforts made at territorial levels and provide inputs to aid decision-making by authorities across all three levels of government, while adhering to financial instruments (budgetary programs) and current regulatory frameworks during the study period. The territorial management intervention by the education sector in response to potential disasters is assessed based on achieving physical, budgetary, and performance indicators outlined in Budget Program 0068 "Vulnerability Reduction and Emergency Response to Disasters" since 2013, and the technical standard approved in 2019, "Provisions for Implementing Emergency and Disaster Risk Management in the Education Sector". These guidelines aim to direct actions of decentralized educational management bodies (DRE/GRE/UGEL) and educational institutions under the leadership of the Ministry of Education, in coordinated efforts with the Presidency of the Council of Ministers (PCM), which oversees the national disaster risk management policy. Within this context, this research identifies the "Inadequate performance of the results-based strategy for disaster risk management intervention in Peruvian education" as a problem, analyzing data from 2021 and 2022 for this study. Given the programmatic nature of the study, aligned with current regulations on budget formulation, programming, execution, and evaluation, overseen by the Ministry of Economy and Finance (MEF), it is crucial to note that each regional government (gobierno regional) independently justifies budget allocations for interventions, in direct coordination with their executing units (UE – education). The Ministry of Education respects regional autonomy and does not interfere in these processes. Moreover, managing territorial risk involves a multisectoral, multilevel approach, necessitating a comprehensive understanding of the system's complexity for effective intervention. The education sector operates through a decentralized organizational structure that extends its intervention to the educational community. Thus, addressing risks within this system is integral. Identified causes of the "Inadequate intervention" problem include fragmented governance, inadequate alignment of budgetary and planning processes, poor management of a complex system, and insufficient monitoring and evaluation. These issues hinder preparedness for disasters and lead to a lack of awareness among the educational community regarding necessary preventive measures against hazards. At the territorial level, this prevents decision-makers from responding appropriately to the realities and needs of the population, despite having had a financial strategy since 2013. The study concludes with an innovative proposal aimed at enhancing decision making through high-quality information management concerning the structure and intervention pathway within the education sector, focusing on territorial aspects. This approach aims to generate inputs that will impact the educational community, ultimately ensuring better preparedness and reduced impact of hazards on educational institutions in the future